Pengaruh Intrinsic Motivation, JOB Autonomy, dan Affective Commitment Terhadap Turnover Intention (Kasus pada Rumah Sakit Kasih Ibu Surakarta) - Indriani, Atiek Yuni, Dr. Anton Agus Setyawan, SE, MSi, Drs. M. Farid Wajdi, MM. Ph.D (2016)
There were many researches to identify factors that influenced employees to leave the organization. We hypothesized that intrinsic motivation, job autonomy, and affective commitment were variables negatively related to turnover intention. A sample of 135 nurses in Rumah Sakit Kasih Ibu Surakarta has been involved in this research. Through the multiple linear regression test, the result shows that the hypotheses of intrinsic motivation and affective commitment are negatively related to turnover intention were supported, but the hypothese of job autonomy is negatively related to turnover intention was rejected. This results may have important implications for Rumah Sakit Kasih Ibu to develop the effective work environment and support the employees to have more opportunities of developing themselves. Conslusions were examined considering practical implications for Rumah Sakit Kasih Ibu Surakarta, the employees, and the need for further researches.